SYSTEMATIZING THE THEME COUNTER-RESISTANCE EXERCISES FOR HIGH SCHOOL PHYSICAL EDUCATION THROUGH THE BASIC CONTENT PHYSICAL CONDITIONING GYMNASTICS (Fiep Bulletin - online, 2012)
This study aims to discuss and present contents proposals on counter-resistance exercises which are highly demanded by adolescent students for High School Physical Education classes. It is a bibliographical study with a propositional nature in which the theme was led through the Paraná State guidelines for School Physical Education (PARANÁ, 2008), containing Physical Conditioning Gymnastics – item which the counter-resistance exercises are inserted in – as a basic content. From the necessity of distributing adjacent contents throughout the grades we sought to do so in order to contemplate the increasing in difficulty and complexity levels. The proposed classes take into account every step from the building of alternative equipment with the use of recyclable material to the comprehension of exercise programs structuring. We conclude that the theme is filled with relevance to adolescents’ lives and should therefore be treated in Physical Education for High School as well as teachers ought to be able to perform so through planning actions and appropriate educational methodologies.
Keywords: Counter-resistance exercises; School Physical Education; High School